Intracyclic velocity signal as a tool to evaluate propulsive phase duration - Schnitzler, C.; Ernwein, V.; Seifert, L.; Chollet, D. (Biomechanics and Medicine in Swimming X, 2006)
This paper examines how intracyclic velocity Signals may be helpful in determining propulsive phase duration in front crawl swimming, serving, thus, as a basis for Index of Coordination (WC) calculation. Nine swimmers performed two experimental tasks: (i) swimming with one arm at maximal speed and (ii) swimming at eight individual swim paces. Video analysis was mixed with the intracyclic velocity signal. The duration of the propulsive phase was then determined visually and using the Inversion of acceleration as determined from the velocity Signal. The results indicated a gap between the beginning and end of the propulsive phase as determined visually and the same propulsive phase measured from the velocity signal. Thus, the visual method gave lower IdC values. However, the adoption of one or the other method has no significant impact on the assessment of the magnitude of coordination change within swim paces. It was concluded that IdC could be calculated with or without the help of the intracyclic velocity signal.